APPSIM - Modelling Education - Percival, R; Payne, A; Harding, A (My University, 2008)
With the partnership of the Australian Research Council and 13 Commonwealth departments, NATSEM is developing a dynamic microsimulation model to project Australia’s future – the Australian Population and Policy Simulation Model (APPSIM). The model will ‘age’ a simulated Australian population by forecasting the life paths of individuals and families from 2001 to 2050, providing a tool for the analysis of the distributional and revenue impacts of policy into the future. A key module of the APPSIM model is education, which will model individuals’ educational participation and qualifications in school, TAFE and university studies. This working paper provides a review of the methods used to model education in existing dynamic microsimulation models from around the world, and an initial proposal for how Australia’s education system could be modelled in APPSIM. Available data on education in Australia is also reviewed.
National Centre for Social and Economic Modelling (NATSEM), University of Canberra, Working Paper
NATSEM Working Paper Series
Keywords: Education and Training; Learning, education and training; Education and Training; Learning, education and training